Hybrid Energy Harvesters: A Fully Functional Universal Self‐Chargeable Power Module for Portable/Wearable Electronics and Self‐Powered IoT Applications (Adv. Energy Mater. 48/2020). Issue 48 (22nd December 2020) - Maharjan, Pukar; Bhatta, Trilochan; Cho, Hyunok; Hui, Xue; Park, Chani; Yoon, Sanghyuk; Salauddin, Md; Rahman, Muhammad Toyabur; Rana, SM Sohel; Park, Jae Y.
Abstract : In article number 2002782, Jae Y. Park and co‐workers develop a universal self‐chargeable power module to efficiently harvest random low frequency and low acceleration vibration energy from human motion, water‐wave motion, and automobile vibration. By implementing multiple spring mechanical coupling, a flexible flux‐concentrator, and electrospun nanofibers, the power module delivers a high DC output power of 34.11 mW which can easily power wearable/portable electronics and sensors.